(untitled) (Altre Modernità, 2021)
Miguel Rocha Vivas, Arca e Ira. Con/versaciones en tiempos de deshumanización (Guadalajara, Editorial Universidad de Guadalajara, 2019, 288 pp. ISBN 978-607-547-675-9) por Simone Ferrari